Functional diversity and metabolic profile of microbial community of mine soils with different levels of chromium contamination. Issue 4 (3rd July 2020) - Pradhan, Sukanta Kumar; Kumar, Upendra; Singh, Nihar Ranjan; Thatoi, Hrudayanath
ABSTRACT: Microbial communities provide useful information about any chemical and physical changes in the environment and play an essential role in maintaining soil fertility. Biolog® eco-plates method was used to study the functional diversity of microbial communities, and their correlation with soil organic carbon (OC), microbial biomass and activities, under three different soil conditions of Sukinda chromite mining area of Odisha, India during August 2016. The OC, available nitrogen, available phosphorus and available potash were significantly ( p  < 0.05) lower in in situ and overburden soils as compared to forest soil. The average development rate of average well color development values decreased with incubation time in all soil conditions. The utilization of six categories of carbon sources by soil microbes decreased with the increase in chromium load and biplot analysis suggested that carbohydrate, polymer and amino acid utilizing microbes were dominant in mining soils. The ecotoxicological status of chromite mine soil would be useful for formulating strategies of possible bioremediation program.